The effect of educational intervention on knowledge and interest in early breast cancer detection among women of reproductive age in Jakarta: a quasi-experimental study - Silvia Yanita Karina; Noorwati Sutandyo; Sabarinah; Popy Yuniar; Asma Fauziah (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Breast cancer is the second most common cancer globally after lung cancer, with 2.2 million new cases in 2020, and Asia accounts for the highest incidence (42.9%). In Indonesia, it is the most prevalent malignancy with 66,000 new cases and the highest cancer-related mortality in 2020, projected by GLOBOCAN to increase to 76,552 by 2030. Most cases are diagnosed at advanced stages, contributing to poor survival, and incidence among younger women continues to rise. This study assessed knowledge and interest in early breast cancer detection among women of reproductive age in Jakarta and evaluated the perceived benefit of educational interventions using booklets and animated videos. A quasi-experimental pre-post test design was conducted with 400 women aged 18–55 years without breast cancer history, recruited from socioeconomically diverse communities, including fishing areas, railways, markets, offices, factories, and residential neighborhoods, and affiliated with religious and women’s community organizations. Participants completed pre-intervention surveys, received education on risk factors, breast self-examination (BSE/SADARI), clinical breast examination (CBE/SADANIS), diagnostic procedures, and prevention promotion, followed by post-intervention surveys. A total of 99.8% of participants perceived the intervention as beneficial. Knowledge scores significantly improved postintervention (p = 0.000), while screening interest showed no significant change (p = 0.581). Knowledge correlated weakly but significantly with interest (p = 0.023, r = 0.120) and age (p = 0.017, r = 0.120), strongly with education (p = 0.000, r = 0.525), and positively with income before and after intervention (p = 0.000). These findings indicate that educational interventions effectively improve knowledge of early detection but may not directly increase screening interest, which is influenced by various factors. Optimizing early detection programs remains crucial to improve prognosis through earlier diagnosis and treatment.